Penyebab Kegagalan Mediasi dalam Proses Perceraian (Studi Kasus di Pengadilan Agama Kudus periode Januari-April 2017) - Supardi Supardi; Zahrotul Hanifiyah (YUDISIA : Jurnal Pemikiran Hukum dan Hukum Islam, 2017)
Family problems are part of the dynamics of marriage. Problems experienced by a married couple can be, in a certain case, a natural process for strengthening the marital relationship, but in other case, it canbe a trigger of household rift,which leads to a divorce. While married couples are experiencing many domestic problems leading to divorce, Islamic law and positive law in Indonesia have recommended the need for reconciliation between the two disputing parties, which is commonly called as the mediation process. This study aims to investigate the implementation of mediation process of divorce cases in the Religious Court of Kudus Regency and explore what factors have caused the failure of the mediation process in the divorce process.